EFFICACY OF “HUANGQI GUIZHI WUWU TANG” COMBINED WITH LASER ACUPUNCTURE IN THE TREATMENT OF LOWER EXTREMITY PERIPHERAL NEUROPATHY CAUSED BY TYPE 2 DIABETES (Vietnam Journal of Community Medicine, 2026)
Background: Lower extremity peripheral neuropathy is the most common chronic complication in patients with type 2 diabetes. The integration of traditional medicine with modern medicine aims to enhance clinical efficacy and minimize complications; however, supportive clinical evidence is required.Objective: To evaluate the efficacy of “Huangqi Guizhi Wuwu Tang” combined with laser acupuncture and Thioctic Acid in treating lower extremity peripheral neuropathy caused by type 2 diabetes.Methods: A clinical intervention study, using pre- and post-treatment comparison with a control group, was conducted on 80 patients with lower extremity peripheral neuropathy caused by  type 2 diabetes. The study group received “Huangqi Guizhi Wuwu Tang,” Thioctic Acid (600mg), and laser acupuncture; the control group received Thioctic Acid (600mg) and laser acupuncture. The treatment course lasted 21 days and was conducted at Tue Tinh Hospital from February to August 2025.Results: After 21 days of treatment, the study group showed significantly better outcomes than the control group in terms of improvement in total UKST score, SF-36 score, 2-hour postprandial blood glucose level, and lower extremity nerve conduction velocity. The VAS scores in both groups decreased significantly (p < 0,05). No side effects were reported.Conclusion: “Huangqi Guizhi Wuwu Tang” combined with laser acupuncture and Thioctic Acid is a safe and effective method for treating lower extremity peripheral neuropathy caused by  type 2 diabetes.
Keywords: Huangqi Guizhi Wuwu Tang, laser acupuncture, lower extremity peripheral neuropathy, type 2 diabetes, traditional medicine.